Ethics of Islamic Education in the 21st Century: Sociological Perspectives in Muhammadiyah Review - Naim, Muhsin; Istanto, Istanto (Proceeding ISETH (International Summit on Science, Technology, and Humanity), 2025)
This study examines the dynamics of Islamic education ethics in the 21st century through a sociological perspective, with a focus on the framework of Muhammadiyah educational thought and practice. In the context of globalization and massive digital disruption, Islamic education faces sociological challenges in the form of a shift in values towards materialism, a crisis of digital morality, and a weakening of social cohesion. The method used is qualitative descriptive with a literature study approach, which includes a systematic synthesis of academic literature, Muhammadiyah policy documents, and classical and contemporary sociological theories to analyze the interaction between social structure and educational value systems. The results of the study show that sociologically, Islamic education not only functions as a transfer of religious knowledge, but also as an agent of the integration of moral values that maintains order and social solidarity in an increasingly rational and individualistic society. Muhammadiyah responds to the challenges of the 21st century by actualizing Al-Ma'un Theology which emphasizes social sensitivity and the principle of Tajdid (renewal), so that educational institutions remain adaptive to technology without losing their spiritual identity. Muhammadiyah's educational ethics consistently internalize the values of honesty, trust, and moderation (Wasathiyah) to form the character of students who have moral integrity and global competence. The findings of this study confirm that the relevance of Muhammadiyah education lies in its ability to harmonize intellectual progress with universal responsibility and welfare. Strengthening Islamic ethics through a sociological approach is crucial for Muhammadiyah in producing a generation of "Progressive Insan" who are able to face the social complexities of the 21st century while still adhering to essential prophetic values.